201k views
1 vote
Using f(x) = 2x - 3 and g(x) = 5, find f(g(3)).7530None of the choices are correct.I don’t think my answer is right please help me thank you

Using f(x) = 2x - 3 and g(x) = 5, find f(g(3)).7530None of the choices are correct-example-1
User Enricoza
by
5.2k points

1 Answer

7 votes

As per given by the question,

There are given that function,


\begin{gathered} f(x)=2x-3,\text{ } \\ g(x)=5 \end{gathered}

Now,

Find the value of f(g(3)).

Then,

There are given that,


g(x)=5

And,

According to question, value of x is 3, that means g(3).

So,

Put the value of x in g(x).

Then,


\begin{gathered} g(x)=5 \\ g(3)=5 \end{gathered}

Now,

For find the value f(g(3));

Put the value of g(3) in the above condition,

f(g(3)).

So,


f(x)=2x-3

Instead of x in f(x), put the g(3).

Then,


\begin{gathered} f(g(3))=2x-3 \\ f(5)=2*5-3 \\ f(5)=10-3 \\ f(5)=7 \end{gathered}

So, the value of f(g(x)) is 7.

Hence, the option first is correct.

User Erad
by
5.6k points